KARAKTERISTIK DAN MOTIVASI WISATAWAN NUSANTARA BERKUNJUNG KE PANTAI BATU MEJAN, BADUNG - Valdiarta Poerba, Gilrandie; Sendra, I Made; Sudiarta, I Nyoman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024), 2024)
It is crucial for tourism managers to pay attention to the characteristics and motivations of tourists, influenced by internal driving factors and external attraction factors. Driving factors originate from within individuals, while attraction factors may come from outside the tourists or specific allurements of the tourist destination. The objective of this research is to comprehend the characteristics and motivations of Indonesian tourists visiting Batu Mejan Beach. The operational definition of variables encompasses Tourist Characteristics and Tourist Motivations, with characteristics divided into Tourist Descriptor and Trip Descriptor, and motivations divided into driving factors and attraction factors. The research method involves observation, literature review, documentation, and the use of questionnaires through Google Form to collect data. Purposive sampling is employed to designate 100 respondents as the sample, and data analysis is conducted using quantitative descriptive analysis with Likert scales. The research findings indicate that visits to Batu Mejan Beach are predominantly by female tourists from Jakarta, aged 17-24, and unmarried. Their primary motivation is to relax and appreciate the natural beauty of Batu Mejan Beach. The managers of Batu Mejan Beach are expected to enhance attention to the cleanliness of toilets, dining areas, and provide trash bins to support an increase in tourist visits and motivate repeat visits.